2002
DOI: 10.1002/aic.690481222
|View full text |Cite
|
Sign up to set email alerts
|

Calcined calcium magnesium acetate as a superior SO2 sorbent: I. Thermal decomposition

Abstract: The reacti®ity of the calcination product of calcium magnesium acetate CMA as a possible dry desulfurization agent was e®aluated. The first step in the dry desulfurization reactionᎏ the thermal decomposition of CMA ᎏ was in®estigated by determining the decomposition reaction in three steps: 1. the e®aporation of water starting at 65ЊC, 2. the con®ersion of CMA into CaCO and MgO starting at 275ЊC, and 3. the decomposi-3 tion of CaCO to CaO starting at 580ЊC. The pseudo-first-order kinetic equation was 3 obser®e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Consequently, the decomposition of the carbonate salts occurred more easily in comparison with CC. Thus, the residual metal oxide gained a bigger core diameter and specific surface area, which could facilitate the desulfurization process [25]. This result is in agreement with the literature.…”
Section: Cp and CC Thermal Decomposition Characteristicssupporting
confidence: 39%
“…Consequently, the decomposition of the carbonate salts occurred more easily in comparison with CC. Thus, the residual metal oxide gained a bigger core diameter and specific surface area, which could facilitate the desulfurization process [25]. This result is in agreement with the literature.…”
Section: Cp and CC Thermal Decomposition Characteristicssupporting
confidence: 39%
“…CaCO 3 is the residue matter for all OCCs; moreover, MgCO 3 is another residue for MCMA, which can be decomposed at lower temperature. The large porosity and internal surface area are generated upon the removal of the organic matters during the decomposition reaction (Han and Sohn, 2002); this significantly improves the sulfur fixation ability of residue at high temperature of stage III. Besides, the mass loss of CP in stage II is 39.47%, which is the higher than that of MCMA, suggesting that the combustible content of CP is higher.…”
Section: Samplesmentioning
confidence: 45%
“…Calcium-containing materials, mostly based on calcium carbonate and calcium hydroxide, are the most commonly used adsorbents for in situ removal of SO x , and consider being a simpler and cheaper method to control SO x emission in coal combustions at the power plant site. 1,2 Recently, some studies indicated that CaO particles derived from organic calcium salts, such as calcium acetate (CA) and calcium magnesium acetate (CMA) demonstrated the unique properties with a large internal surface area for in situ removal of SO x . 3,4 However, producing the organically bonded calcium by the reactions of lime or calcium hydroxide with the conventional acetic acid makes these adsorbents more expensive than the natural ones and commercial uses impossible.…”
Section: Introductionmentioning
confidence: 40%
“…The mechanism gives a good fit for previous experiment data of the decomposition of calcium carbonate in previous literature. 29 The values of E a at this stage resulted to be 137.035 kJ/mol, 116.297 kJ/mol and 112.834 kJ/mol for CA, CEB10 and CEB12, respectively, which were far lower than that of calcite decomposition (about 163-250 kJ/mol 1,30 ). Therefore, it is easy to understand that CEB10 exhibits a little higher calcination rate than CA at this decomposition stage.…”
mentioning
confidence: 46%